The Umayyads the rise of Islamic art (Arte islamica nel Mediterraneo, 2000)
An excellent resource for digging deeper into the art and architecture at most of the major tourist attractions in Jordan. It proposes several itineraries that a traveler could cover during a trip to Jordan.